Βιβλιοκρισία:AL. BUCOSSI – AL. RODRIGUEZ-SUAREZ (eds.), John II Komnenos, Emperor of Byzantium: In the Shadow of Father and Son [Centre for Hellenic Studies, Publications 17], London – New York: Routledge 2016 - ΜΑΥΡΟΜΜΑΤΗ Καλλιόπη Ν. (Byzantina Symmeikta, 2019)
Βιβλιοκρισία:Al. Bucossi – Al. Rodriguez-Suarez (eds.), John II Komnenos, Emperor of Byzantium: In the Shadow of Father and Son [Centre for Hellenic Studies, Publications 17], London – New York: Routledge 2016